Clinical features and outcomes of pregnancies complicated by coexisting gestational diabetes and hypertensive disorders - Jia, Chaoying; Bo, Lanying; Xiao, Shu; Du, Shunlan (Frontiers in Medicine, 2025)
BackgroundGestational diabetes mellitus (GDM) and hypertensive disorder complicating pregnancy (HDP) share pathophysiological mechanisms that increase the risk for adverse maternal and neonatal outcomes. However, their combined impact remains underexplored.ObjectiveTo assess the clinical characteristics, therapeutic interventions, and maternal–fetal outcomes in pregnancies complicated by both GDM and HDP.MethodsA retrospective study was conducted involving 82 women with GDM complicated by HDP and 118 healthy pregnant controls. Clinical parameters, mode of delivery, and pregnancy outcomes were compared between groups. Logistic regression analysis was performed to identify independent predictors of GDM complicated by HDP.ResultsWomen with GDM complicated by HDP exhibited significantly higher pre-pregnancy weight, body mass index (BMI), fasting blood glucose, triglycerides, and high-density lipoprotein (HDL) cholesterol compared with healthy controls (p < 0.05). Logistic regression identified these variables as independent predictors of GDM + HDP (p < 0.001). The GDM + HDP group also had higher rates of cesarean delivery and adverse pregnancy outcomes. Individualized treatment targeting glycemic and blood pressure control significantly improved metabolic parameters and reduced the incidence of complications (p < 0.05).ConclusionPre-pregnancy metabolic factors, including BMI, fasting blood glucose, triglycerides, and HDL cholesterol, are strong predictors of GDM complicated by HDP. Early identification and individualized management of these high-risk pregnancies can effectively reduce adverse maternal and neonatal outcomes.